A mid-Cretaceous land snail Euthema truncatellina sp. nov. (Caenogastropoda, Cyclophoroidea, Diplommatinidae) from Burmese amber - Balashov, Igor A.; Perkovsky, Evgeny E.; Vasilenko, Dmitry V. (Zootaxa, 2020)
Diplommatinidae Pfeiffer, 1857 is a speciose family of minute operculate land snails that includes more than 500 extant species occurring mainly in Southeastern Asia and northern Oceania with some species in tropical America and, arguably, in Madagascar (Kobelt 1902; Wenz 1938-1939; Haas 1961; Egorov. 2013; Yamazaki et al. 2013; Neubert & Bouchet 2015; Nurinsiyah & Hausdorf 2017; Páll-Gergely et al. 2017a; Greke, 2017). The fossil record of Diplommatinidae is very sparse; it was recorded from the Miocene of Poland (Harzhauser & Neubauer 2018) and four species were recently described from Cretaceous Burmese amber, being the oldest known diplommatinids (Yu et al. 2018; Hirano et al. 2019; Bullis et al. 2020).